Discrepancies in cornell scale for depression in dementia (CSDD) items between residents and caregivers, and the CSDD's factor structure - Nahathai Wongpakaran (2018)
Purpose: This validation study aims to examine Cornell Scale for Depression in Dementia (CSDD) items in terms of the agreement found between residents and caregivers, and also to compare alternative models of the Thai version of the CSDD. Patients and methods: A cross-sectional study was conducted of 84 elderly residents (46 women, 38 men, age range 60-94 years) in a long-term residential home setting in Thailand between March and June 2011. The selected residents went through a comprehensive geriatric assessment that included use of the Mini-Mental State Examination, Mini-International Neuropsychiatric Interview, and CSDD instruments. Intraclass correlation (ICC) was calculated in order to establish the level of agreement between the residents and caregivers, in light of the residents' cognitive status. Confirmatory factor analysis (CFA) was adopted to evaluate the alternative CSDD models. Results: The CSDD yielded a high internal consistency (Cronbach's alpha = 0.87) and moderate agreement between residents and caregivers (ICC = 0.55); however, it was stronger in cognitively impaired subjects (ICC = 0.71). CFA revealed that there was no difference between the four-factor model, in which factors A (mood-related signs) and E (ideational disturbance) were collapsed into a single factor, and the five-factor model as per the original theoretical construct. Both models were found to be similar, and displayed a poor fit. Conclusion: The CSDD demonstrated a moderate level of interrater agreement between residents and caregivers, and was more reliable when used with cognitively impaired residents. CFA indicated a poorly fitting model in this sample. © 2013 Wongpakaran et al.